AN ANALYSIS ON MALCOLM RIVER’S DISSOCIATIVE IDENTITY DISORDER IN IDENTITY MOVIE DIRECTED BY JAMES MANGOLD - Wibowo, Abdul RohimIndra (LANTERN (Journal on English Language, Culture and Literature), 2017)
This project aims to analyze the character Malcolm River in Identity movie. The result of analyzing the figures Malcolm Riversis that he suffered multiple personality syndrome or now known as Dissociative Identity Disorder. Malcolm was abused, neglected, and finally abandoned by his mother was a prostitute whenhe was a child.He felt extremely insecure so he made a new personality or a new identity to protect his original identity. However, this new identity was in fact a killer. As time goes on he made new identities to fight against the identity of the killer and also protect him from any threat.